2003
DOI: 10.1590/s0074-02762003000400020
|View full text |Cite
|
Sign up to set email alerts
|

Candida dubliniensis identification in Brazilian yeast stock collection

Abstract: We investigated the presence of Candida dubliniensis among isolates previously identified as Candida albicans and maintained in a yeast stock collection from 1994 to 2000. All isolates were serotyped and further evaluated for antifungal susceptibility profile. After doing a screening test for C. dubliniensis isolates based on the capability of colonies to grow at 42°C, its final identification was obtained by randomly amplified polymorphic DNA (RAPD) analysis using three different primers. A total of 46 out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
11

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
2
12
0
11
Order By: Relevance
“…C. albicans serotype-A was the most prevalent phenotype of C. albicans isolates in both groups studied. This result is in accordance with previous reports (Sant 'Ana et al 2002, Mariano et al 2003. Analysis of ubiquinone systems and nucleotide sequences of D1/D2 regions of LSUrDNA -When the authors attempted to identify the yeasts isolated from the oral cavities of HIV-infected patients by using conventional methods, some isolates were difficult to identify.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…C. albicans serotype-A was the most prevalent phenotype of C. albicans isolates in both groups studied. This result is in accordance with previous reports (Sant 'Ana et al 2002, Mariano et al 2003. Analysis of ubiquinone systems and nucleotide sequences of D1/D2 regions of LSUrDNA -When the authors attempted to identify the yeasts isolated from the oral cavities of HIV-infected patients by using conventional methods, some isolates were difficult to identify.…”
Section: Resultssupporting
confidence: 89%
“…Interestingly, no C. dubliniensis isolates were found in our study. C. dubliniensis isolates have been rarely reported in South America, which includes Brazil and Argentina (Rodero et al 1998, Sano et al 2000, Mariano et al 2003) with low incidence of 1.5-2% compared with 14% incidence in worldwide reports (Sullivan et al 1995, Pinjon et al 2003. Rare Candida spp.…”
Section: Resultsmentioning
confidence: 99%
“…C. dubliniensis isolates exhibited MIC values of 0.125 µg/mL for voriconazole. C. dubliniensis isolates from Brazil in a previous study (10) reported high susceptibility for azoles and similar results were described in the literature (13,18,19). Nondubliniensis isolates from the other members of the family were susceptible to all drugs tested (data not shown).…”
Section: Resultssupporting
confidence: 88%
“…The prevalence of C. dubliniensis isolates in determined populations remains uncommon in HIV-infected patients 19,23,25 . The absence of this species above related, of C. glabrata and only one C. krusei isolate in our group may be explained by the subjects' exposure lack to antifungal agents during the previous three months.…”
Section: Discussionmentioning
confidence: 99%